Isso dá pra aprender!: a dança na Educação Integral - Juliana Araujo de Paula (2017)
Understanding the learning processes of dance in the context of the Integrated School Program (PEI) of the Municipal Network of Belo Horizonte is the objective of this paper. In order to describe and analyze the learning of dance, this paper counted on the focus of situated learning in practice communities (LAVE and WENGER, 1991) and the perspective of the education of attention (INGOLD, 2010). The study addresses learning as an inherent aspect of all social practice (LAVE and WENGER, 1991). From an ethnographic incursion into the universe of everyday urban dances practices in the context of PEI, this paper sought to reveal how the learning processes take place. In addition, interviews were conducted with the children who were part of the research group and with the Dance Teacher. The collectivity was fundamental in this process that involved, besides the school, other time and spaces, such as the experiences on the street, with groups and at home. The skill of the dance was constituted from the immersion in practice and, mainly, of the repetition and imitation. The dancer's constitution was continually given in that process in which dance (and its learning) emerged. It was, therefore, the construction of identities that in this specific case was the black identity.